Estimation of fatigue parameters in total strain life equation for powder metallurgy superalloy FGH96 and other metallic materials. (May 2019) - Wang, Yanrong; Wang, Xuechao; Zhong, Bo; Wei, Dasheng; Jiang, Xianghua
Highlights: A new method to obtain the parameters in the total strain equation is presented. Monotonic tensile and LCF tests of FGH96 are conducted at elevated temperature. The proposed method offered is validated by experiment results for FGH96. The predicted results with the proposed model are better. Abstract: Monotonic tensile and low cycle fatigue (LCF) tests of powder metallurgy (PM) superalloy FGH96 were conducted at 480 °C and 650 °C. The alloy was widely used to manufacture the aero-engine turbine disk by a process of hot isostatic pressing (HIP). An analysis method was proposed to obtain the fatigue parameters of the total strain equation with clearly physical meaning. The proposed method offered satisfied results for FGH96. Fractography analysis was conducted to determine the material fatigue failure mechanisms. Comparing to the given parameters of total strain life equation of the handbook, the predicted fatigue lives of GH4169 alloy at 500 °C and 650 °C, FGH95 alloy at 500 °C and TC4 alloy at 200 °C by the proposed method agreed better with the experimental results.